Leptin and leptin receptor expression in breast carcinomas and their relationship with clinicopathological features - Irem Atalay Karacay; Arsenal Sezgin Alikanoglu; Dinc Suren; Banu Ozturk; Baris R. Karakas; Cem Sezer (Elsevier, 2022)
Context: Breast cancer is the most common cancer and the most common cause of death from cancer among women. Leptin is thought to play role in cell proliferation. Objective: In this study, we evaluated the expression of leptin and leptin receptor in breast cancer and normal breast tissue, analyzed the relationship between expression of leptin, leptin receptor and clinicopathological features in breast cancers. Materials and Methods: The expression of leptin and leptin receptor were investigated by immunohistochemistry in 205 breast cancer and 30 normal breast tissue. Results: Breast cancers showed higher expression of leptin (p = 0,003) and leptin receptor (p < 0,001) than normal breast tissues. The expression of leptin showed significant correlation with leptin receptor expression (r = 0,644; p < 0,001). Higher rates of ER and PR positivity are found in leptin positive tumors(p < 0,001). Expression levels of leptin were positively corelated with ER (r = 0,336; p < 0,001) and PR (r = 0,359; p < 0,001) expression. HER2 positivity rates were lower in leptin positive tumors (p = 0,020). Negative correlation between leptin expression levels and histological grade was found (r = -0,168; p = 0,016). Higher rates of leptin receptor positivity were detected in invasive ductal carcinoma NSTs than invasive lobular carcinomas. Conclusion: Elevated expressions of leptin and leptin receptor levels in breast cancer tissues suggest that leptin may have a promoting effect on the carcinogenesis of breast cancer, possibly in an autocrine manner. Inhibition of leptin may be effective for the treatment of breast cancer.